Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae) - Freyhof, Jörg; Turan, Davut (Zootaxa, 2019)
Alburnus magnificus, new species, is described from the northern Orontes River drainage in the eastern Mediterranean Sea basin. It is most similar and closely-related to A. qalilus from coastal rivers in Syria south of the Orontes. Alburnus magnificus is distinguished from A. qalilus by having the anal-fin origin below or behind the vertical through the last dorsal-fin ray, 4–5 scale rows between the lateral line and the anal-fin origin, and a flank pattern of bold black, grey or brown scales on a silvery or brown background. The two species are also distinguished by a minimum K2P distance of 1.8% in their COI sequence data.